A Descriptive Study of Adolescent Lifestyle and Cardiovascular Disease Risk in Senior High School - Wayunah, Wayunah; Anwar Huda, Syaefunnuril; Saefulloh, Muhammad (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Introduction: Common adolescent behaviors such as consuming fast food, high-sugar beverages, lack of physical activity, and excessive screen time are major contributing factors to the emergence of CVD among youth. Early detection of risk factors during adolescence is essential to prevent the progression of CVD later in life. Objective: This study aims to describe CVD risk factors among high school students. Method: A descriptive design, data were collected through questionnaires distributed to 162 twelfth-grade students at a public senior high school in Tasikmalaya, using accidental sampling. Data were analyzed using descriptive statistics (frequency and percentage). Result: The average age was 17 years, with the majority being female (63%). A total of 89.5% of respondents lived in urban areas, 63% showed a tendency toward light physical activity, 58.6% consumed junk food 1–2 times per week, 18.5% had a smoking habit, and 63% experienced significant stress. Conclusion: These findings indicate that adolescents' current lifestyle is prone to CVD risk factors. Integrated interventions through health education in school and family environments are necessary to raise awareness of the importance of a balanced diet, adequate physical activity, and effective stress management to prevent the future development of CVD.